THE IMPACT DISTRIBUTIVE JUSTICE, PROCEDURAL JUSTICE, INTERACTIONAL JUSTICE, EMPLOYEE ENGAGEMENT AND JOB SATISFACTION ON TURNOVER INTENTION - Suhartatik, Ani; Junaedi, C. Marliana; Novianti, Putri Meidina (RIMA - Research In Management and Accounting, 2020)
The research is aimed at investigating the impact distibutive justice, procedural justice,interactional justice, employee engagement and job satisfaction on turnover intention.. Hence, it is a causal research. The data are drawn from a sample ofÂ  208 bank employees in Surabaya determined using a purposive sampling technique. The collected data are then analyzed using Structural Equation Modeling, LISREL version 8.70. The result of the hypothesis testing indicates that distibutive justice and procedural justice does not have any significant impact on employee engagement and job satisfaction, interactional justice have any significantly affect on employee engagement and job satisfaction, employee engagement significantly affect on turnover intention, and job satisfaction significantly affect on turnover intention